2009
DOI: 10.2106/jbjs.h.00439
|View full text |Cite
|
Sign up to set email alerts
|

Periprosthetic Humeral Fractures During Shoulder Arthroplasty

Abstract: The data from the present study suggest that although intraoperative humeral fractures are associated with a high rate of healing, there was a substantial rate of associated complications, including transient nerve injuries and fracture displacement. Significant risk factors for intraoperative fractures include female sex, revision surgery, and press-fit humeral implants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
113
0
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 206 publications
(116 citation statements)
references
References 28 publications
2
113
0
1
Order By: Relevance
“…To avoid potentially severe complications, the anterior circumflex vessels were ligated in four cases since then. Intraoperative periprosthetic fractures are rare: Athwal et al reported an incidence of 1.5% in a combined series of primary total shoulder arthroplasty, hemiarthroplasty, and revision total shoulder arthroplasty, 42% of them involving solely the greater tuberosity [1]. The fractured greater tuberosity in our series can be explained by the fact that the C-block osteotomy weakens the proximal humerus by interrupting the subcapital cortical ring, and by the osteopenic condition of this specific patient with sickle cell anemia.…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…To avoid potentially severe complications, the anterior circumflex vessels were ligated in four cases since then. Intraoperative periprosthetic fractures are rare: Athwal et al reported an incidence of 1.5% in a combined series of primary total shoulder arthroplasty, hemiarthroplasty, and revision total shoulder arthroplasty, 42% of them involving solely the greater tuberosity [1]. The fractured greater tuberosity in our series can be explained by the fact that the C-block osteotomy weakens the proximal humerus by interrupting the subcapital cortical ring, and by the osteopenic condition of this specific patient with sickle cell anemia.…”
Section: Discussionmentioning
confidence: 52%
“…The fractured greater tuberosity in our series can be explained by the fact that the C-block osteotomy weakens the proximal humerus by interrupting the subcapital cortical ring, and by the osteopenic condition of this specific patient with sickle cell anemia. Although these fractures are associated with a high rate of healing [1], as in our patient, it is advisable to handle the proximal humerus with extreme care to prevent this complication.…”
Section: Discussionmentioning
confidence: 71%
“…Periprosthetic fractures associated with anatomic shoulder arthroplasty are relatively uncommon, with an incidence between 0.6% and 3% [1,6,8,9,12,15,18,19,[24][25][26].…”
Section: Introductionmentioning
confidence: 99%
“…Although not studied as comprehensively as postoperative fractures, the incidence, risk factors, and outcomes associated with intraoperative periprosthetic fractures during anatomic shoulder arthroplasty has been characterized [1,19]. The rate of intraoperative fractures during revision primary anatomic arthroplasty is as much as 3.3% [1].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation